Hubungan Pre Eklampsia Pada Ibu Hamil dengan Kejadian BBLR di RSUD Kelas D Pondokgede - Netri Makassar; Elfira Sri Futriani (Malahayati Nursing Journal, 2024)
ABSTRACT According to the World Health Organization (WHO) the infant mortality rate (AKB) in the world is still quite high, which is 37 per 1000 live births. One of the causes of high infant mortality (AKB) in the world is low birth weight (BBLR). The factors that cause BBLR are maternal factors, fetal factors, placental factors, and environmental factors, one of the mother's factors is Pre Eclampsia. This research aims to find out "The Relationship of Pre-Eclampsia in Pregnant Women with BBLR Incidents in Pondokgede Class D Hospital". The population in this study is a maternity mother who was recorded in the register, namely as many as 60 mothers and a sample of 33 mothers. The cross sectional approach method is a study at the data collection stage carried out at one point in time (ati onei pointi this time), while those studied are during one data collection period (Swarjana, 2015). Data analysis using chi square. The chi square test results show that the pre chi square test results show that the pre eclampsia and maternal age value p value 0.000 and 0.004 so that there is a statistical relationship with BBLR. It is hoped that interventions can be carried out to reduce the incidence of BBLR based on causal factors such as giving KIE to couples, counseling about the consumption of fe tablets and how to store them, HB screening for WUS and adolescents, ANC regularly during pregnancy and consuming healthy and nutritious food. The results of the statistical test were obtained with a P value of 0.000, so it can be concluded that there is a "pre-eclampsia relationship in pregnant women with the BBLR incident at the Pondokgede Class D Hospital". Keywords: Preeclampsia, Mother's Age, BBLR  ABSTRAK Menurut Organisasi Kesehatan Dunia (WHO), angka kematian bayi (AKB) di seluruh dunia masih cukup tinggi 37 per 1.000 kelahiran hidup. Salah satu penyebab tingginya angka kematian bayi (AKB) di seluruh dunia adalah berat badan lahir rendah (BBLR). Faktor penyebab BBLR adalah faktor ibu, faktor janin, faktor plasenta, dan faktor lingkungan. Salah satu faktor ibu adalah preeklampsia. Tujuan penelitian ini adalah untuk mengetahui “hubungan antara pre eklampsia pada ibu hamil dengan kejadian BBLR di RSUD D Pondokgede”. Populasi pada penelitian ini merupakan ibu bersalin yang tercatat pada register yaitu sebanyak 60 ibu dan sampel 33 ibu Metode pendekatan cross sectional adalah penelitian pada tahap pengumpulan data dilakukan pada satu titik waktu (ati onei pointi ini time), adapun yang diteliti yaitu selama satu periode pengumpulan data (Swarjana, 2015). Analisis data menggunakan chi square. Hasil uji chi-square menunjukkan hasil uji pre eklampsia dan usia ibu mempunyai nilai p-value sebesar 0,000 dan 0,004 sehingga terdapat hubungan statistik dengan BBLR. Diharapkan dapat dilakukan intervensi untuk menurunkan kejadian BBLR berdasarkan faktor penyebab seperti pemberian KIE pada pasangan suami istri, edukasi konsumsi dan penyimpanan tablet Fe, skrining BBLR pada WUS dan remaja, serta pemeriksaan kehamilan rutin. .selama pengobatan untuk memperkecil kehamilan dan pola makan yang sehat dan bergizi. Dari hasil penelitian ini dapat disimpulkan bahwa terdapat “Hubungan Pre Eklampsia Pada Ibu Hamil Dengan Kejadian BBLR Di RSUD Kelas D Pondokgede”. Kata Kunci: Preeklampsia, Usia Ibu, BBLR